(untitled) (Annals of Medical Research, 2021)
Aim: A study was carried out in human patients with suspicion of cystic echinococcosis. Echinococcosis granulosus is a zoonotic disease that causes cystic echinococcosis in humans and animals. The disease caused by adult or larval stages of tapeworms of the genus Echinococcus family.Material and Methods: 1,102 blood samples sent to Erzincan Binali Yıldırım University, Mengücek Gazi Training and Research Hospital Medical Microbiology Laboratory between January 2011 and December 2018 with suspicion of cystic echinococcosis were centrifuged at 1500 rpm for 10 minutes. Serum samples were tested immediately by indirect hemagglutination test in order to detect specific antibodies.Results: 248 of 1,102 blood samples of patients were found to be infected with cystic echinococcosis for the 9-year of period (an average annual incidence of 10.48 per 100,000 inhabitants). Conclusion: It is understood that hydatid disease is decreasing in the province, but there is always a risk of increases in cystic echinococcosis for humans.